1996
DOI: 10.1021/jp960347h
|View full text |Cite
|
Sign up to set email alerts
|

Potential Surfaces for Unimolecular and Bimolecular Gas Phase Reactions of BHmCln Calculated at the G2 Level of Theory

Abstract: Transition structures and reaction paths for the BH m Cl n system have been characterized at the MP2(full)/6-31G(d) level of theory; heats of reaction and barriers have been computed at the G2 level of theory. Calculations show that the insertion reactions of BH m Cl n into H 2 and HCl (m + n ) 0, 1, 2) occur by highly distorted, non-least motion transition states, with barriers that increase with chlorine substitution on boron. Hydrogen abstraction from BH and BH 3-n Cl n by chlorine proceeds with little or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 24 publications
7
27
0
Order By: Relevance
“…TS 1A is a three‐membered ring transition structure, and is formed by the insertion of the lone electron pair of the S atom into the BH empty p‐orbital and the attachment of one H atom of H 2 S to the BH σ‐electron pair; TS 1B is a four‐membered ring transition structure and is formed by the insertion of the lone pair of the S atom of H 2 S into the BH empty p‐orbital and the simultaneous Coulombic attraction between the H atom of the BH molecule and one H atom of the H 2 S molecule. The similar three‐ and four‐membered transition structures were also found in the reactions of BH+NO 5 and BH+HCl 15 systems. IRC calculations confirmed that TS 1A connected the addition complex HB:SH 2 and the product H 2 BSH, and that TS 1B connected the addition complex HB:SH 2 and the product BSH+H 2 .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…TS 1A is a three‐membered ring transition structure, and is formed by the insertion of the lone electron pair of the S atom into the BH empty p‐orbital and the attachment of one H atom of H 2 S to the BH σ‐electron pair; TS 1B is a four‐membered ring transition structure and is formed by the insertion of the lone pair of the S atom of H 2 S into the BH empty p‐orbital and the simultaneous Coulombic attraction between the H atom of the BH molecule and one H atom of the H 2 S molecule. The similar three‐ and four‐membered transition structures were also found in the reactions of BH+NO 5 and BH+HCl 15 systems. IRC calculations confirmed that TS 1A connected the addition complex HB:SH 2 and the product H 2 BSH, and that TS 1B connected the addition complex HB:SH 2 and the product BSH+H 2 .…”
Section: Resultssupporting
confidence: 70%
“…Such well‐known examples as CH, BH, SiH, and AlH have been the subject of active investigation both experimentally and theoretically 1–17. Among these monovalent hydrides, BH and AlH, as two homologous compounds, are particularly interesting because their singlet states have one σ‐electron pair and two empty p‐orbitals, respectively, so they are both nuclephile in the direction of the σ‐orbital and electrophile in the direction of the empty p‐orbital, which result in their complex reactivities in interaction with small polar molecules such as HCl, HF, H 2 O 7, 15–17. These reactions have common characters—there are two parallel reaction channels: one is an addition reaction via the three‐membered ring transition state and the other is a dehydrogenation reaction via the four‐membered ring transition state.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the results observed in B 2 H 6 /He/H 2 systems. The minor production of B atoms in the absence of a H 2 flow suggests that the direct product is B(CH 3 ) 2 or BCH 3 , from which B atoms are formed in the following exothermic addition-elimination processes: H + B(CH 3 ) 2 → HB(CH 3 ) 2 → BCH 3 + CH 4 + 135 kJ and H + BCH 3 → HBCH 3 → B + CH 4 + 67 kJ, which are similar to those for H + BH x → HBH x → BH x−1 + H 2 reactions [3,13,14]. The CH 4 signals observed in the mass spectrometric measurements in the presence of a H 2 flow are consistent with the presence of these processes.…”
Section: Detection Of B Atoms In B(ch 3 ) 3 /H 2 Systemssupporting
confidence: 56%
“…However, electronspin-resonance ͑ESR͒ spectroscopy studies [35][36][37] show the existence of the BH 4 radical and it is suggested that the lone electron interacts strongly with two equivalent H atoms. In addition full electronic structure calculations [38][39][40] reveal that the ground state of the BH 4 radical has a C 2 symmetry. The predicted BH 4 radical geometry 40 using the MP2/6-311+ +G͑d , p͒ method is found to agree well with those by the ReaxFF HBN and B3LYP/ 6 -311G ** calculations.…”
Section: A Bond Dissociationmentioning
confidence: 99%